The Influence Of Profitability, Liquidity, Growth Opportunity, Capital Structure On Company Value - Nurdin, Nurdin (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
This study aims to examine the Effect of Profitability, Liquidity, Growth Opportunity, Capital Structure on the Value of Companies in the mining sub-sector listed on the Indonesia Stock Exchange. The period used in this study is from 2015 to 2019. This research is causal associative with a quantitative approach measured by multiple linear regression-based methods with SPSS. The population of this study is the mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019. The sample was determined using the purposive sampling method. Based on the existing criteria, a sample of 10 companies was obtained so that the total observations in this study were 50 observations. The data used in this study used secondary data. The data collection technique uses the documentation method through the official website of each company and through the official IDX website: www.idx.co.id. The results of this study indicate that (1) Profitability has a positive effect on Firm Value, (2) Liquidity has an effect on Firm Value, (3) Growth Opportunity has a positive effect on Firm Value, (4) Capital Structure has a positive effect on firm value.